Hubungan Antara Pengetahuan dan Sikap Keamanan Pangan dengan Bias Optimis pada Penjamah Makanan di Kantin SMA Negeri di Kota Magelang, Indonesia: The Association Between Food Safety Knowledge and Attitude with Optimistic Bias among Food Handlers in Senior High School Canteens in Magelang City, Indonesia - Budiningsari, Dwi; Prawiningdyah, Yeni; Prianto, Joko; Sekarsari, Kivani Amalia; Khoirunisa', Ayu (Universitas Airlangga, 2024)
Background: Foodborne diseases are a significant global concern, with food available in educational institutions being a common source of food poisoning in Indonesia. The lack of attention to hygiene and sanitation by food handlers is a key factor, often influenced by optimistic bias, resulting in insufficient focus on proper food processing and serving procedures. Objectives: To examine the correlation between food safety knowledge and attitudes with optimistic bias in food handlers in five State High Schools canteens, Magelang City. Methods: This cross sectional study included a total of 41 food handlers who work at the canteens of five State High School, Magelang City. The independent variables were food safety knowledge and attitudes, while the dependent variable was optimistic bias. The categories of food safety knowledge variable consist of good and poor food safety knowledge. Food safety attitudes was categorized as positive attitudes and negative attitudes. The categories of variable optimistic bias consist of high, possible, and low optimistic bias. The Spearman correlation test was conducted. Results: The results of the correlation test between food safety knowledge and attitudes with optimistic bias among food handlers in five State High School canteens, Magelang City showed p-value= 0,704 and 0,498. Conclusions: Food safety knowledge and attitudes are not significantly correlated with optimistic bias among food handlers in five State High School canteens, Magelang City. Food safety training supervised by public health office is needed to improve the quality of service.